Subject-orientation as design language for integration across organisational control layers - Neubauer, Matthias; Krenn, Florian; Majoe, Dennis; Stary, Christian (International journal of production research, 2017)
Recent research and development in production industry reveals a movement to cyber-physical production systems and Internet of things enabled manufacturing. In this context, ways in which enterprise processes are conceptualised and executed are changing. Decentralising production by applying interlinked cyber-physical production resources breaks up the traditional boundaries between different process abstraction layers. Heterogeneous smart devices and processes at all levels in the industrial control need to interact in such systems. In this paper, requirements from the field of Business Process Management towards the vertical integration of business and production processes are derived. With respect to the identified requirements the eligibility of the Subject-oriented Process Management (S-BPM) approach for vertical process integration is depicted. At the core, the paper investigates the applicability of S-BPM to achieve vertical process integration and reports lessons learnt from two industrial application scenarios. The first scenario aims to encode human properties to adapt workplaces to human needs. The second scenario aims towards supporting the execution and tracking of dynamic production processes.